The India way : how India's top business leaders are revolutionizing management - Cappelli, Peter; Singh, Harbir; Singh, Jitendra; Useem, Michael (Boston, Mass. : Harvard Business Press, 2010)
"Over the last two decades, many of India's leading companies have been achieving double-digit growth - even in the midst of a global recession. Understanding what is driving the Indian business juggernaut is an imperative no manager - in any part of the world - can afford to ignore." "In this timely book, professors Peter Cappelli, Harbir Singh, Jitendra Singh, and Michael Useem of the Wharton School India Team reveal the secrets of India's top-performing companies: an innovative, unconventional, and exportable set of management principles they call the "India Way." The authors argue that the India Way could have the same remarkable impact that Japanese business leaders and the "Toyota Way" had on manufacturing around the world: it could change the practice - and purpose - of management on a global scale." "Drawing on interviews with more than one hundred top executives from India's largest corporations - including Infosys Technologies, Reliance Industries, and Tata Sons - the authors reveal how the India Way differs from Western management practice in how organizations manage and value employees; transcend barriers through improvisation; create compelling value propositions that serve a massive, underprivileged market; govern for the long term; and make social issues a business priority. The authors identify how managers in other countries can learn from these practices and adapt them in their own companies."--BOOK JACKET.
Keywords: Management; Corporate culture; Corporate governance